ETHICAL ASPECTS IN CLINICAL TRIALS IN CHILDREN - Arnaudova Danevska, Ivana; Arnaudov, Dimitar; Jakjovska, Tatjana; Boshkovska, Katerina; Momchilovikj, Sonja; Gjinovska Tasevska, Elena (Македонско лекарско друштво = Macedonian Medical Association, 2021)
Conducting clinical trials in children has particular importance as they strive to provide optimal care and therapy for this specific group of patients, but their implementation is still complex. This is often due to the lack of agreed-upon research objectives, unresolved questions about informed consent, and the general perception that children are a vulnerable group of subjects. For providing the best clinical care for pediatric subjects, it is important to conduct careful, effective research that has a scientific basis to answer important clinical questions. The main challenge of pediatric research is the risk and therefore the question arises whether the purpose of the research justifies the risks associated with the study? The four ethical principles should serve as a framework in the process of conducting clinical trials in children: benefacere, justice, respect for personality and confidentiality. One principle is no more or less important than the others, so all four must be taken into account when conducting a research. The ethical principle of "respect for personality" is the basis for the process of informed consent. It is a legal document by which the patient voluntarily agrees to participate in a research. The informed consent must be signed by child's legal guardian(s) and this step cannot be delegated to other family members or friends unless there is a legal basis. However, with proper planning and monitoring the study process, a research can be conducted in children even though they are considered as a vulnerable population.
ЕТИЧКИ АСПЕКТИ НА КЛИНИЧКИ ИСТРАЖУВАЊА НА ДЕЦА
Keywords: clinical research; informed consent; children; participation